The performance of N(1,1-dimethylpropynyl-3,5-dichlorobenzamide) and other herbicides in controlling weeds in lettuce as affected by soil type and weather conditions - Mitidieri, Agustín (Oregon State University, 1970)
Tesis de maestría para obtener el grado de Magister of Science presentada en Oregon State University en junio de 1970